A emenda constitucional 33/01 e o "novo" ICMS - importação: manutenção da "transferência de titularidade" como núcleo constitucional da materialidade do ICMS - importação - Leão, Cristiano Maciel Carneiro (2007)
The present work has the purpose of analyzing the amendments to the 1988 Federal Constitution resulting from the Constitutional Amendment n.º 33/2001, more specifically as regards to the ICMS Importation [State Goods and Services Circulation Tax]. As it is known, it is not a new matter that the States and the Federal District are trying to collect the ICMS Importation on every and any entrance of assets or goods to the country. They were lacking only the indispensable constitutional authorization in order to do that. The legislator of the aforementioned Amendment, on its side, tried to make effective the intention of the States and the Federal District, taking steps for the amendment of the constitutional archetype of the ICMS Importation so as such tribute could be collected at the time of every and any importation, regardless the nature of the operation arranged abroad, who/which is fostering it and, finally, the utilization to be given to the imported assets. It seems to us that the intention, as referred to, was very successful as regards to some of its purposes as the newest ICMS Importation can be collected by means of the in abstracto tribute levying as regards to assets or goods, not taking into account the utilization that will be given to them. However, the purpose of the Constitutional Amendment n.º 33/01 was not fully reached. This problem so happened because the Amendment had not the ability of modifying the archetype of the ICMS Importation so as such exaction could have an incidence over merely physical circulations. Due to that reason, it is our conclusion, and the conclusion of the present work, that in spite of the modification as implemented by the Constitutional Amendment n.º 33/01 regarding the ICMS Importation, the exaction, as referred to, may not have an incidence over mere physical circulation, but only over operations that have to do with juridical circulation that is made effective only with the transfer of the ownership of the asset or good